On‐Surface Synthesis of Porous Carbon Nanoribbons on Silver: Reaction Kinetics and the Influence of the Surface Structure. Issue 18 (3rd September 2019) - Ammon, Maximilian; Haller, Martin; Sorayya, Shadi; Maier, Sabine
Abstract: We report on the influence of the surface structure and the reaction kinetics in the bottom‐up fabrication of porous nanoribbons on silver surfaces using low‐temperature scanning tunneling microscopy. The porous carbon nanoribbons are fabricated by the polymerization of 1, 3, 5‐tris(3‐bromophenyl)benzene directly on the Ag surface using an Ullmann‐type reaction in combination with dehydrogenative coupling reactions. We demonstrate the successful on‐surface synthesis of porous nanoribbons on Ag(111) and Ag(100) even though the self‐assemblies of the intermediate organometallic structures and covalently‐linked polymer chains are different on both surfaces. Furthermore, we present the formation of isolated porous nanoribbons by kinetic control. Our results give valuable insights into the role of substrate‐induced templating effects and the reaction kinetics in the on‐surface synthesis of conformationally flexible molecules. Abstract : Tie a carbon ribbon round : We demonstrate the on‐surface synthesis of porous carbon nanoribbons on Ag(111) and Ag(100) even though the self‐assemblies of the organometallic intermediates and intermediate covalent chains are different on both lattices.